Flowers, labour and territory: the study of Cotopaxi - Martinez, Luciano (2014)
This article discusses the proletarianization process in the largely rural province of Cotopaxi, with specific reference to areas where flower production for export has become the most important economic activity. The young labor force members employed by the industry tend to spend their income on non-productive consumption because they own no land or because land is very scarce. Even though precarious employment does not appear to be present, levels of organization and social capital formation remain low. The transformation that has taken place in this area in just a few years points to the consolidation of a business model whose dynamics arise from the world market.